A model for the inner jet high-energy emission of Centaurus A - Orellana, Mariana Dominga (2010)
We investigate the spectral energy distribution (SED) of Centaurus A resulting from a steady compact acceleration region, located close to the central black hole, where both leptonic and hadronic relativistic populations arise. We present here results of such a model, where we have considered synchrotron radiation by primary electrons and protons, inverse Compton scattering, and gamma-ray emission originated by the inelastic hadronic interactions between relativistic protons and cold nuclei within the jets. Photo-meson production by relativistic hadrons were also taken into account, as well as the effects of secondary particles injected by all interactions. The internal and external absorption of gamma-rays is shown to be of great relevance to shape the observable SED, which was also recently constrained by the results of Fermi and HESS.